2022
DOI: 10.20944/preprints202201.0457.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating Transfer Learning in Graph Neural Networks

Abstract: Graph neural networks (GNNs) build on the success of deep learning models by extending them for use in graph spaces. Transfer learning has proven extremely successful for traditional deep learning problems: resulting in faster training and improved performance. Despite the increasing interest in GNNs and their use cases, there is little research on their transferability. This research demonstrates that transfer learning is effective with GNNs, and describes how source tasks and the choice of GNN impact the abi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Transfer learning has proven successful for traditional deep learning problems. Kooverjee et al ( 2022 ), recently demonstrated that transfer learning is effective with GNNs and compared the performances of graph convolution networks (GCN) and graphSAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer learning has proven successful for traditional deep learning problems. Kooverjee et al ( 2022 ), recently demonstrated that transfer learning is effective with GNNs and compared the performances of graph convolution networks (GCN) and graphSAGE.…”
Section: Discussionmentioning
confidence: 99%